A close eye on the eagle-eyed visual acuity hypothesis of autism - Bölte, Sven (Journal of autism and developmental disorders, 2011)
Autism spectrum disorders (ASD) have been associated with sensory hypersensitivity. A recent study reported visual acuity (VA) in ASD in the region reported for birds of prey. The validity of the results was subsequently doubted. This study examined VA in 34 individuals with ASD, 16 with schizophrenia (SCH), and 26 typically developing (TYP). Participants with ASD did not show higher VA than those with SCH and TYP. There were no substantial correlations of VA with clinical severity in ASD or SCH. This study could not confirm the eagle-eyed acuity hypothesis of ASD, or find evidence for a connection of VA and clinical phenotypes. Research needs to further address the origins and circumstances associated with altered sensory or perceptual processing in ASD.